THE INFLUENCE OF A FOLK CREATION ON A PHYSICAL EDUCATION A CHILD’S - Залізняк, Алла (Modern engineering and innovative technologies, 2023)
The subject of the article is an important factor of physical education are folk creation. There is a positive physical activity on the functional state of the human body. Prosaic and poetic folklore is selected. An actual problem of physical education